REGULATION OF THE CREDIT MARKET OF UKRAINE - Зорянський, Віталій (Socio-economic relations in the digital society, 2019)
In a changing environment in the lending market, banks and lending institutions are increasingly creating new products to compete with other market players. One of the main principles for the further development and functioning of a new product in the credit market is the attitude of the regulator (the National Bank of Ukraine) to this innovation. Since this attitude will depend on the further state of the fi nancial market of the country, and ultimately it will affect the consumer. An attempt to introduce P2P lending in the banking system of Ukraine indicates that the National Bank of Ukraine is not yet ready to accept online lending, and accordingly, under this direction of lending, create a regulatory framework that would satisfy the main key aspects of banking in this segment. That is why it is expedient to study the foreign experience of equal lending and consider the advantages and disadvantages of such lending for the fi nancial system of Ukraine.